Case report: Significant relief of linezolid-induced peripheral neuropathy in a pre-XDR-TB case after acupuncture treatment - Mo, Yuping; Zhu, Zhu; Tan, Jie; Liang, Zhilin; Wu, Jiahui; Chen, Xingcheng; Hu, Ming; Zhang, Peize; Deng, Guofang; Fu, Liang (Frontiers in Neurology, 2022)
The revised WHO guidelines on multidrug- or rifampicin-resistant tuberculosis (MDR/RR-TB) include linezolid in the core drug group. Common adverse events of prolonged linezolid use are bone marrow suppression and peripheral neuropathy (PN). Available measures against linezolid-induced PN (LIPN) often have insignificant effects, leading to linezolid discontinuation and a decline in the success rate of MDR/RR-TB treatment. Acupuncture treatment is a symptomatic treatment measure from traditional Chinese medicine (TCM) to relieve pain with overall very low evidence and has never been reported in LIPN. The pilot use of acupuncture in a pre-XDR-TB (a more severe form of MDR/RR-TB) patient exhibited significant improvements in LIPN and thus maintained linezolid in the regimen for a longer period.